Karakteristik On Street Parking di Badan Jalan Pada Ruas Jalan Merdeka Selatan Kota Malang - Petrus Fahik; Andy Kristafi Arifianto; Blima Oktaviastuti (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
Parking is an important element in urban transportation because it affects transportation mode choices and has both short-term and long-term impacts on society and the transportation system. Jalan Merdeka Selatan in Malang City features parking that can be categorized into two types: on-street parking and off-street parking. This study aims to identify the characteristics of on-street parking along Jalan Merdeka Selatan, Malang City. Indicators for measuring the characteristics of on-street parking include traffic volume, road geometry, capacity, speed, degree of saturation, and level of service. The research design uses a quantitative approach with descriptive research type. The results show a decrease in average vehicle speed and an increase in congestion due to on-street parking, which reduces road capacity. On-street parking on Jalan Merdeka Selatan causes a decrease in average vehicle speed by up to 20%, traffic volume increases during peak hours, significantly raising congestion levels, and on-street parking disrupts traffic flow and safety.